2016
DOI: 10.1002/2015gb005337
|View full text |Cite
|
Sign up to set email alerts
|

Eroding permafrost coasts release low amounts of dissolved organic carbon (DOC) from ground ice into the nearshore zone of the Arctic Ocean

Abstract: Ice-rich permafrost coasts in the Arctic are highly sensitive to climate warming and erode at a pace that exceeds the global average. Permafrost coasts deliver vast amounts of organic carbon into the nearshore zone of the Arctic Ocean. Numbers on flux exist for particulate organic carbon (POC) and total or soil organic carbon (TOC, SOC). However, they do not exist for dissolved organic carbon (DOC), which is known to be highly bioavailable. This study aims to estimate DOC stocks in coastal permafrost as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 86 publications
0
49
1
Order By: Relevance
“…A major process is the dilution and mixing with melted massive ice beds that underlie the RTS or ice wedges that intersect the permafrost exposures in the headwall. Both consist of nearly pure ice (~99%), contain very low amounts of OC, and take up~28% of the total sediment volume at our study site (Couture and Pollard, 2015;Fritz et al, 2015;Tanski et al, 2016). With initial slumping, the massive ice melts and dilutes OC derived from the active layer and thawed permafrost, partially explaining the loss of OC in the disturbed zone.…”
Section: Processes After Initial Slumpingmentioning
confidence: 89%
See 2 more Smart Citations
“…A major process is the dilution and mixing with melted massive ice beds that underlie the RTS or ice wedges that intersect the permafrost exposures in the headwall. Both consist of nearly pure ice (~99%), contain very low amounts of OC, and take up~28% of the total sediment volume at our study site (Couture and Pollard, 2015;Fritz et al, 2015;Tanski et al, 2016). With initial slumping, the massive ice melts and dilutes OC derived from the active layer and thawed permafrost, partially explaining the loss of OC in the disturbed zone.…”
Section: Processes After Initial Slumpingmentioning
confidence: 89%
“…Leaching of POC is supported by the studies of Artinger et al (2000), who reported that DOC in the form of humic acids can originate from sediment OC, as well as by Dou et al (2008) who showed that different solutions have the potential to leach DOC from POC. Tanski et al (2016) showed a very strong correlation between sediment contents and DOC concentrations within massive ice, most likely due to prolonged contact of meltwater during segregation. Also, showed that DOC can be taken up by water flowing over thermokarst into the ocean.…”
Section: Processes After Initial Slumpingmentioning
confidence: 97%
See 1 more Smart Citation
“…This flux is 4 orders of magnitude lower than the tDOC supply from the Mackenzie River specified as boundary conditions in the model (2.54 Tg C yr −1 ). Similarly, tDOC eroded from permafrost stored in the North American shores accounts for only ∼ 0.5-1.6 × 10 −4 Tg C yr −1 (Tanski et al, 2016;Ping et al, 2011, using a DOC : particulate organic carbon, POC, ratio of 1 : 900 as in Tanski et al, 2016) to ∼ 2 × 10 −3 Tg C yr −1 (McGuire et al, 2009). With regard to these flux values, tDOC originating from both melted sea ice and eroded permafrost, not taken into account in the model, are hence not believed to explain the model-satellite discrepancies (Fig.…”
Section: Tdoc Concentrations and Distributionmentioning
confidence: 99%
“…We estimated mobilized SOC and DOC stocks and fluxes from RTSs based on the values provided in Couture (2010) and Tanski et al (2016). OC values were derived from in-situ measurements (Tanski et al, 2016;Couture, 2010) and were available for each coastal segment.…”
Section: Estimates Of Soil and Dissolved Organic Carbon Valuesmentioning
confidence: 99%